2010
DOI: 10.2215/cjn.02960410
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Blood Pressure, and African Americans

Abstract: Vitamin D deficiency has increasingly been recognized in the general population and especially in African Americans whose deep skin pigmentation makes vitamin D photosynthesis inefficient. Over the last decade there has been increasing interest in the role that vitamin D deficiency may play in BP modulation because many epidemiologic studies have shown an inverse association between serum vitamin D concentration and BP. There is a high prevalence of vitamin D deficiency in African Americans who also have an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
0
30
0
1
Order By: Relevance
“…38 Because the melanin in skin pigmentation absorbs sunlight in wavelengths important to the conversion of 7-dehydrocholesterol into pre-VitD, 39 individuals of nonwhite race/ethnicity are more likely to have VitD insufficiency than white individuals of northern or central European ancestry. 2 Hypovitaminosis D not only is relevant to cognition but may also promote other health risks such as hypertension 40,41 and cardiovascular disease, 42 2 diseases particularly prevalent among African American and Hispanic individuals and associated with increased dementia risk. 43 However, recent evidence from the Copenhagen Heart Study suggests that VitD deficiency may be specific to AD risk, as vascular dementia was not associated with low VitD status.…”
Section: Discussionmentioning
confidence: 99%
“…38 Because the melanin in skin pigmentation absorbs sunlight in wavelengths important to the conversion of 7-dehydrocholesterol into pre-VitD, 39 individuals of nonwhite race/ethnicity are more likely to have VitD insufficiency than white individuals of northern or central European ancestry. 2 Hypovitaminosis D not only is relevant to cognition but may also promote other health risks such as hypertension 40,41 and cardiovascular disease, 42 2 diseases particularly prevalent among African American and Hispanic individuals and associated with increased dementia risk. 43 However, recent evidence from the Copenhagen Heart Study suggests that VitD deficiency may be specific to AD risk, as vascular dementia was not associated with low VitD status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the antihypertensive properties of vitamin D include renoprotective effects, suppression of the renin-angiotensin-aldosterone system, direct effects on vascular cells, and effects on calcium metabolism (63). Interestingly, the high prevalence of vitamin D deficiency in African Americans beginning at an early age (26) and persisting throughout life may play a major role in the genesis and maintenance of hypertension (64). Although it is our contention that this group is at increased risk because of their high prevalence of vitamin D deficiency, there are no data to suggest that Caucasian adults and children with vitamin D deficiency would be at lesser risk (64).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the high prevalence of vitamin D deficiency in African Americans beginning at an early age (26) and persisting throughout life may play a major role in the genesis and maintenance of hypertension (64). Although it is our contention that this group is at increased risk because of their high prevalence of vitamin D deficiency, there are no data to suggest that Caucasian adults and children with vitamin D deficiency would be at lesser risk (64). However, additional evidence is required before recommending widespread vitamin D supplementation in the primary prevention of hypertension (16), in particular in the young.…”
Section: Discussionmentioning
confidence: 99%
“…However, only recently has it been thoroughly scrutinized; not surprisingly, the specialized antirickets hormone emerged as a multifunctional endocrine, paracrine/autocrine molecule with a broad spectrum of functions. Vitamin D seems to influence the expression of more than 200 genes, in addition to exerting its classical regulatory effects on mineral homeostasis, vitamin D seems to be integrated in the physiological control of cell proliferation [2,3], blood pressure [4,5], cardiac function [6,7], immunomodulation [8,9], muscle performance [10e12], and aging [13,14] and has a complex influence on the regulation of energetic metabolism [15,16]. Over the last few years, there has been great interest in delineating the physiological role of vitamin D in each of these functions and also its participation in the emergence of disorders such as cancer, hypertension, diabetes mellitus, and obesity.…”
Section: Introductionmentioning
confidence: 99%